L2 Accentedness and Language Self-Esteem in Foreign Language Learning - Szyszka , Magdalena (Research in Language, 2022)
Accentedness is associated with listeners’ evaluative judgements, which might affect an L2 speaker’s construction of an image about linguistic self-worth and competence, described as language (L2) self-esteem. This line of inquiry is pursued in the study presented in this paper, which investigates the relationship between L2 self-esteem and the extent to which a learner’s L2 pronunciation differs from a listener’s representation of it – accentedness. The results show that the level of L2 self-esteem correlates with accentedness, and the direction of this correlation is negative (r = -.51). The findings also reveal that the L2 self-esteem levels of the participants whose accentedness is closer to native-like are significantly higher than those of the individuals with strongly accented speech.